Revolutionising broiler nutrition: The role of probiotics, fermented products, and paraprobiotics in functional feeds - Harsh Kumar; Indu Bhardwaj; Eugenie Nepovimova; Daljeet Singh Dhanjal; Sumayya Sana Shaikh; Renáta Knop; David Atuahene; Ayaz Mukarram Shaikh; Kovács Béla (Journal of Agriculture and Food Research)
Advancements in nutrition, inheritance, housing management, and research on chicken well-being and welfare have driven growth in poultry production. However, the unregulated use of antibiotic growth promoters has led to antibiotic resistance and drug residues, prompting several nations, including European Union members, to ban antibiotics in animal feed. Researchers have focused on safe alternatives such as probiotics, fermented probiotics products, and paraprobiotics. Therefore, nowadays normal diet is supplemented with probiotics that act as an immunomodulator which effectively sustains the healthy microbiota, regulate different blood parameters and enhances meat quality. Moreover, the feeding of probiotics-fermented plant-based food with basal diet provides a double benefit to chicken health as it gets the benefits from probiotics as well as dietary polyphenols. Finally, the addition of paraprobiotics increases the overall gut immunity in the broiler chickens.